Codonopsis pilosula Polysaccharide Attenuates Tau Hyperphosphorylation and Cognitive Impairments in hTau Infected Mice - Zhang, Qing; Xia, Yiyuan; Luo, Hongbin; Huang, Sheng; Wang, Yongjun; Shentu, Yangping; Mahaman, Yacoubou Abdoul Razak; Huang, Fang; Ke, Dan; Wang, Qun; Liu, Rong; Wang, Jian-Zhi; et al. (Frontiers in Molecular Neuroscience, 2018)
Codonopsis pilosula Polysaccharide (CPPs), a natural products with potentially lower toxicity and better bioavailability has been used in traditional Chinese medicine for thousands of years and a neuroprotective polysaccharide mitigates tau pathology in AD mouse model. However, whether CPPs can relieve AD pathology and cognitive defects remains poorly understood. Here we reported that CPPs remarkably increased the cell viability and PP2A activity, decreased tau phosphorylation in HEK 293/tau cells. Next, we employed an adeno-associated virus serotype 2 (AAV2)-induced expression of human full length tau (hTau) in C57/BL6 mice to mimic AD tau pathology. One month intragastric administration of CPPs significantly increased PP2A activity and reduced tau phosphorylation at Ser199, Ser202/Thr205 (AT8) and Thr231 in hippocampus of hTau mice. Furthermore, behavioral tests revealed that CPPs rescued hTau overexpression induced cognitive defects while CPPs significantly increased the fEPSP slope and synaptic proteins including synaptotagmin and synaptophysin. Together, our data suggest that CPPs might prevent AD-like tau hyperphosphorylation via activation of PP2A and attenuates AD-like cognitive impairments through restoring the synaptic plasticity and synaptogenesis. In conclusion, these findings provide the first evidence supporting that CPPs might be a potential candidate compound for the prevention of cognitive decline and increased risk for AD and tau related diseases.